Pengaruh Kualitas Pelayanan dan Kepuasan Pelanggan terhadap Loyalitas Pelanggan Studi pada Alfamart Jetis, Kec. Nusawungu Kab. Cilacap - Riyono Riyono; Hesti Ristanto; Ahmad Dwi Nurdianto (Global Leadership Organizational Research in Management, 2024)
The purpose of this study aims to determine : 1) To determine and explain the influence of service quality on Alfamart Jetis customer loyalty. 2) To find out and explain the influence of customer satisfaction on Alfamart Jetis customer loyalty. 3) To find out and explain the influence of service quality and customer satisfaction on Alfamart Jetis customer loyalty. The approach used in this research is a quantitative approach, this research is included in the hypotheticoductive method, meaning that the research in this research is a process that begins with observation in the form of preliminary observations of phenomena in business administration in the form of collecting initial data.This research method uses Purposive Sampling and Accidental Sampling techniques. Accidental Sampling means that those used as sample members are customers who happen to be met at the time of data collection. Data was obtained from a questionnaire which was then processed and analyzed using SPSS (Statistical Package for the Social Sciences) software.The research results show that: 1. Service quality has no and no significant effect on customer loyalty. 2. Customer satisfaction has a significant and influential effect on customer loyalty. 3. Service quality and customer satisfaction together have a significant influence on customer loyalty.